Authenticity and the interview: a positive response to a radical critique. (December 2019) - Whitaker, Emilie Morwenna; Atkinson, Paul
We respond to recent discussions of the interview, and the 'radical critique' of interviewing, as reiterated in publications by Silverman and Hammersley. Reviewing and extending the critical commentary on the social life of the interview and its implications for qualitative research, we endorse criticism of the Romantic view of the informant as a speaking subject, arguing that the interview does not give access to the interiority or private emotions of social actors. We focus especially on the search for the 'authentic' voice of experience and feeling, arguing that the expression of authenticity is performative, and that such interviews need to be analysed for their performative features. The biographical work of the interview demands close, formal analysis, and not mere celebration. The argument is illustrated with a single case-study, derived from an ethnographic study of a social-work service in the UK. We suggest that it is possible to derive constructive responses to the radical critique, by adopting an analytic stance towards respondents' biographical work, as expressed through extended, qualitative interviewing. The speaker's use of positioning rhetoric is discussed.